Lying in the scanner: Covert countermeasures disrupt deception detection by functional magnetic resonance imaging - Ganis, Giorgio; Rosenfeld, J. Peter; Meixner, John; Kievit, Rogier A.; Schendan, Haline E. (NeuroImage (Orlando, Fla.), 2011)
Functional magnetic resonance imaging (fMRI) studies have documented differences between deceptive and honest responses. Capitalizing on this research, companies marketing fMRI-based lie detection services have been founded, generating methodological and ethical concerns in scientific and legal communities. Critically, no fMRI study has examined directly the effect of countermeasures, methods used by prevaricators to defeat deception detection procedures. An fMRI study was conducted to fill this research gap using a concealed information paradigm in which participants were trained to use countermeasures. Robust group fMRI differences between deceptive and honest responses were found without, but not with countermeasures. Furthermore, in single participants, deception detection accuracy was 100% without countermeasures, using activation in ventrolateral and medial prefrontal cortices, but fell to 33% with countermeasures. These findings show that fMRI-based deception detection measures can be vulnerable to countermeasures, calling for caution before applying these methods to real-world situations. ► Activation in prefrontal cortex distinguishes lies from truth in single subjects. ► Countermeasures can disrupt single subject FMRI-based deception detection. ► Caution needs to be used in applying these methods in real-world settings.